Answer:
t(n) = 2n² + n - 3
Explanation:
Given sequence:
Find the formula for nth term t(n)
Solution
Sequence is neither arithmetic nor geometric, analyzing:
First level difference
Second level difference
As there are two levels, the formula should be in the form of:
Trying the formula with the known terms:
- t(2) = 4a + 2b + c = 7 ⇒ 3a + b = 7
- t(3) = 9a + 3b + c = 18 ⇒ 3(3a+b) + c = 18 ⇒ 21 + c = 18 ⇒ c = -3
Going back to previous equations to find remaining coefficients:
- t(1) ⇒ a+ b = 3 ⇒ t(2) = 2a + (a+b) = 7 ⇒2a + 3 = 7 ⇒ a= 2 ⇒ b = 1
So the formula becomes:
t(n) = 2n² + n - 3